2016
DOI: 10.1371/journal.pone.0159003
|View full text |Cite
|
Sign up to set email alerts
|

An Acoustic Analysis of the Genus Microhyla (Anura: Microhylidae) of Sri Lanka

Abstract: Vocalizing behavior of frogs and toads, once quantified, is useful for systematics, rapid species identification, behavioral experimentation and conservation monitoring. But yet, for many lineages vocalizations remain unknown or poorly quantified, especially in diversity rich tropical regions. Here we provide a quantitative acoustical analysis for all four Sri Lankan congeners of the genus Microhyla. Three of these species are endemic to the island, but Microhyla ornata is regionally widespread. Two of these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first to report the advertisement call of M. beilunensis consisting of 2-7 pulses per call, which has relatively few NPs among the 29 studied Microhyla species. Similar to that in other Microhyla species reported previously (Wijayathilaka, Meegaskumbura & Gianni, 2016;Sun, 2017;Nguyen et al, 2019;Poyarkov et al, 2019;Garg et al, 2018), oscillograms and spectrogram of advertisement calls in M. beilunensis were conformed to the pulse-repetition sound based on Beeman's (1998) sound categories. The patterns of variation in call parameters of anurans are correlated with female preferences and different parameters contain different kinds of biologically significant information (Gerhardt, 1991).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…To the best of our knowledge, the present study is the first to report the advertisement call of M. beilunensis consisting of 2-7 pulses per call, which has relatively few NPs among the 29 studied Microhyla species. Similar to that in other Microhyla species reported previously (Wijayathilaka, Meegaskumbura & Gianni, 2016;Sun, 2017;Nguyen et al, 2019;Poyarkov et al, 2019;Garg et al, 2018), oscillograms and spectrogram of advertisement calls in M. beilunensis were conformed to the pulse-repetition sound based on Beeman's (1998) sound categories. The patterns of variation in call parameters of anurans are correlated with female preferences and different parameters contain different kinds of biologically significant information (Gerhardt, 1991).…”
Section: Discussionsupporting
confidence: 86%
“…Our results showed that spectral parameters (e.g., DF, F1 and F3) are under the physical body size constraint, with smaller individuals producing calls at higher frequencies; in contrast, temporal parameters were not influenced by body size in the three Microhyla species. Similar results were also found in other Microhyla species (Wijayathilaka, Meegaskumbura & Gianni, 2016) indicating that spectral parameters of calls might encode the information of male's body size in each Microhyla species. Therefore, researchers suggested that the spectral parameters of anurans' advertisement calls, as an honest signal, transfer information about the body size of vocalizing individuals and thus, possibly information about its strength and quality to females and competitors (Davies & Halliday, 1978;Wells, 2007).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The sound files in wave format were resampled at 48 kHz with sampling depth 24 bits. Calls were recoded and examined as described by Wijayathilaka & Meegaskumbura (2016). Call recordings were visualized and edited with SoundRuler 0.9.6.0 (Gridi-Papp 2003-2007 and Raven Pro 1.5 software (Cornell Laboratory of Ornithology, Ithaca, NY, USA).…”
Section: Bioacoustics Analysesmentioning
confidence: 99%
“…A second individual was sighted the next day from the same area. The pulsatile and short advertisement calls of the pool breeder M. ornata (Wijayathilaka & Meegaskumbura 2016) was also heard from another spot in the kitchen-garden area after a heavy downpour on 11 July 2015 when most of the area was waterlogged. …”
Section: Family Microhylidae Günther 1858mentioning
confidence: 98%